Data and computer communications - Stallings, William (Pearson, 2011)
The ninth edition of 'Data and Computer Communications' features improved illustrations, integrated coverage of TCP/IP and Ethernet, a survey of ADSL, new coverage of IP multicasting and reports on the very latest technologies in hardware and software.